(untitled) (Majalah Ekonomi, 2022)
The purpose of this research is to comprehend connection between demographic factors and entrepreneurial motivation of millennial generation in Indonesia. This quantitative research used millennial generation (birth year 1980-2000) in Indonesia as the research population. Using purposive sampling technique, this study obtained total sample of 319 respondents. The data analysis technique used is chi-square. The results showed that there were several demographic factors related to entrepreneurial motivation, namely: gender, age group, marital status, education level, family background, and economic background. With the results of this study, policy makers can pay more attention to demographic backgrounds in developing entrepreneurial programs among the millennial generation. The placement of entrepreneurship programs in the millennial generation group who have a strong entrepreneurial motivation is expected to increase the success rate of the program.